SOCIAL MORALITY EDUCATION IN THE REJANG’S CULTURE OF "SERAMBEAK" - Fakhruddin Fakhruddin (Ta'dib, 2021)
The social morality education contained in Serambeak is a meeting of the sacred mission of Islamic education with the Rejang culture in terms maintaining the life of the Rejang community. The Rejang community lives on the basis of a rural life system that strongly adheres to a set of cultures and customs called Serambeak, which contain social morality education of the community. Thus, this qualitative research was conducted by means of the descriptive-analytic method in a way that the words, sentences, and discourses in the literary work of Serambeak were described, and were, then, analyzed by providing understanding and explanations of texts. Data interpretation was carried out resting upon the researcher’s and community’s perspectives through information shared by traditional and religious leaders. The data analysis technique was carried out by classifying the data based on tracing the sentence clusters in Serambeak through the character's speeches and their   attitudes. The results of this study revealed the following: First, the use of Serambeak as a local culture with its literary beauty makes it easier for the Rejang community to receive the social morality education brought by Islam as a foreign religion. Second, the content of social morality education in Serambeak consists of the arrangement of life for action and demands for action. Third, the social morality education contained in Serambeak is an effort to erode the old life orders, attitudes, and behaviors of Rejang people.